Online Collaborative Activities during Covid-19: Students’ Perception - Mohammed Farrah; Manar Itkaidek; Ameera Dandis (Randwick International of Education and Linguistics Science Journal, 2023)
This study investigates the advantages and disadvantages of online collaborative learning activities as perceived by the English Department students at Hebron University, Palestine. A 34-item questionnaire was used to collect this data. The participants of the study consisted of 61 students at Hebron University. The researchers tried to illustrate the advantages and disadvantages of online collaborative activities and tried to give solutions for the challenges students may face. The results indicate that the students in general express positive attitudes towards the online collaborative activities, as they develop several areas for them. The results also show that the students face several problems in this experience, although they support and try to suggest some solutions to them.